Effective Sampling-Based Assessment Method for Evaluating Electrical Engineering Programme Performance - W. Mansor; B. N. Sheikh Rahimullah; M. N. Taib; N. Mohamad Zaini; M. F. Abdul Latip; A. R. Mahmud (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Challenges in the conventional way of measuring programme outcome include large data sets to be processed, a large amount of manpower, operating cost increment and time consuming. A sampling-based approach to evaluate the performance of a programme is proposed and a mathematical model is developed to determine the overall programme outcome score. The criteria for course selection and percentage of students considered in the assessment, was designed to accelerate the process. The results obtained from the implementation of sampling based approach in the assessment have shown that the programme is successful and the students have achieved the required knowledge and skills. The sampling-based approach is capable of demonstrating the programme and the students’ achievement.